Printed nanocarbon heaters for stretchable sport and leisure garments - Claypole, A.; Claypole, J.; Bezodis, N.; Kilduff, L.; Gethin, D.; Claypole, T. (Materials, 2022)
The ability to maintain body temperature has been shown to bring about improvements in sporting performance. However, current solutions are limited with regards to flexibility, heating uniformity and robustness. An innovative screen-printed Nanocarbon heater is demonstrated which is robust to bending, folding, tensile extensions of up to 20% and machine washing. This combination of ink and substrate enables the heated garments to safely flex without impeding the wearer. It is capable of producing uniform heating over a 15 × 4 cm area using a conductive ink based on a blend of Graphite Nanoplatelets and Carbon Black. This can be attributed to the low roughness of the conductive carbon coating, the uniform distribution and good interconnection of the carbon particles. The heaters have a low thermal inertia, producing a rapid temperature response at low voltages, reaching equilibrium temperatures within 120 s of being switched on. The heaters reached the 40 °C required for wearable heating applications within 20 s at 12 Volts. Screen printing was demonstrated to be an effective method of controlling the printed layer thickness with good interlayer adhesion and contact for multiple printed layers. This can be used to regulate their electrical properties and hence adjust the heater performance.